Development of a Green Downstream Process for the Valorization of Porphyridium cruentum Biomass - Rocío Gallego; Marina Martínez; Alejandro Cifuentes; Elena Ibáñez; Miguel Herrero (Molecules, 2019)
As the interest in biorefinery approaches is continuously increasing, new alternatives for the downstream valorization of biomasses are sought. Porphyridium cruentum microalga is a good natural source for a variety of interesting bioactive compounds, including carotenoids, phycoerythrin, and sulfated polysaccharides. In the present contribution, the use of compressed fluids-based techniques is explored towards the efficient and green extraction of bioactive compounds to valorize microalgal biomass. The extraction of carotenoids was first optimized using pressurized ethanol. The best extraction conditions involved the use of 125 °C for 20 min at 10.5 MPa. Subsequently, a sequential valorization process was devised based on the application of different steps directed towards the extraction of phycoerythrin, sulfated polysaccharides, and carotenoids, respectively. The applied pressurized conditions allowed the attainment of a good recovery of polar components without compromising the stability and extraction of carotenoids. Therefore, the proposed approach could be employed to obtain different bioactives from P. cruentum microalgal biomass employing green extraction processes.